Penerapan Metode TOPSIS Dalam Pemilihan Media Pembelajaran Berbasis Komputer - Rizka, Ade (Forum Kerjasama Pendidikan Tinggi, 2022)
Information technology is one of the needs and has an important role in the field of education. One form of utilizing technological developments in the field of education is through computer-based learning media. Computer-based learning media is a tool that helps the learning process between teachers and students in the digital era. Various types of computer-based learning media are available, but the similarities in the types of variations become obstacles in the selection process. The selection of learning media has several important elements that will determine the suitability of the science and material to be studied. The selection process with a decision support system using several criteria will help in making decisions. The TOPSIS method can identify solutions from available alternatives based on criteria. Elements of learning media which are the criteria for each alternative, namely, sound, images, video, text, animation, graphics, graphics, tutorials, interactive, visual and practical. The media element is an indicator in this research. Based on the application of the method, the results of implementation and testing in the selection process have a more spesific value between each alternative, namely the PPT alternative has a preference value of 0, the CD alternative gas a preference value of 0.4299, the video alternative has a preference value of 1 and the internet alternative has a result preference value 0.6205. Then the TOPSIS methid in selecting computer-based learning media can assist teachers in directing students to choose the type of learning media that is suitable for learning interests. The overall appearance of the system has been adapted to the needs of students to make it easier to understand and use.